Types of tremor in patients with cerebrovascular diseases and cardiovascular events - Petrov, Igor; Mulic, Mersudin; Georgiev, Antonio (Association of medical doctors Sanamed Novi Pazar, 2016)
Introduction: Tremor can occur as a part of the clinical picture of cerebrovascular diseases. Many patients with cerebral stroke have cardiovascular diseases as a comorbidity or complication of stroke; sometimes cardiovascular events can lead to embolic stroke. Aim: To present types of tremor in patients with cerebrovascular diseases and cardiovascular events and diabetes mellitus type 2, clinical characteristics of tremor and investigations used. Material and methods: In our study we included 36 patients, 24 men and 12 women, that were examined and followed for 3 years, from 2012-2015. All patients were subjected to the following investigations: neurological examination, laboratory analysis, computerized tomography of brain, magnetic resonance imaging and electroencephalography. In cardiovascular patients we also performed Doppler sonography of carotid arteries, electrocardiography, cardiac ultrasound. The patients were examined and treated by cardiologists. Results: Of all patients 22% had cerebral infarction, 41% atherosclerosis, 36% multiple lacunar infarctions and 28% diabetes mellitus type 2. Three patients with cerebral infarction had chorea, hemiballismus, dystonia and dystonic tremor, three had postural tremor and two cerebellar intention tremor. Atherosclerotic patients had atherosclerotic action tremor, while diabetic patients predominantly had with action-type tremor. Electroencephalography showed irritative basic brain activity with slow waves, while carotid arteries stenosis was diagnosed by Doppler sonography. Computerized tomography of the brain and magnetic resonance imaging revealed cerebrovascular diseases in certain areas. Patients with cardiomyopathy, rhythm disorders, high blood pressure, was investigated and medically treated by a cardiologist. Conclusion: In cerebrovascular diseases different types of tremor can occur as a result of damage of the extrapyramidal system.
Keywords: tremor; basal ganglia; atherosclerotic tremor; cardiovascular events